Dynamics of Growth, Poverty, and Inequality in Pakistan - Ali, S. S.; Tahir, Sayyid (Pakistan Institute of Development Economics, Islamabad, Pakistan, 1999)
The paper contributes to the existing literature on poverty, and particularly on the analysis of Pakistan’s poverty situation in at least the following four ways: (1) It develops three consistent time series on rural, urban, and total poverty (both at household level and at individual level, which, in fact, makes them six series) that covers all Household Expenditure Surveys that have been conducted so far, thus providing the longest such series developed for Pakistan. 2) It highlights the econometric problems in using the survey data in conjunction with aggregate data on poverty and income to derive the conclusions. It then shows a proper way and applies the method on Pakistan’s data. (3) Unlike most other studies that combine time series and cross section data, it makes an analysis of the relationship between poverty and growth, between inequality and growth, and interaction between these three variables in the context of a single developing country. (4) It provides long-run elasticities of poverty with respect to growth and inequality which are useful for policy purposes. Some policy conclusions that are obtained from this systematic analysis.